Economic Efficiency of Selected Financial System Institutions of Local Government - Urszula Rabiej (Prawo Budżetowe Państwa i Samorządu)
Functioning of local government units, as for as the economic sphere is concerned, is based on the financial law regulations. Those regulations aim at solving economic and social problems. The analysis of economic efficiency concerning implemented regulations is of particular importance for changing the EU’s attitude towards the influence, which EU has on functioning of the local governments. Implementing the local budgets, based on regulations which economic efficiency hasn’t been evaluated on the stage of legislation, may have a negative impact on local community and the economic situation of the country. Frequent changes of financial law cause actions, which financial effects cannot be predicted. What is more, those unstable regulations make it impossible to plan essential parts of a budget in a right way. That has a great importance in terms of correctness of long-term financial perspectives of the local government units.